ALTERNATIVE STUDY PRESTRESSED BEAMS AT THE MOUTH OF THE BAY BRIDGE INTERCHANGE LERONG SAMARINDA - RAMADANI, BASUKI (KURVA S JURNAL MAHASISWA, 2016)
Capability and reliability for a bridge is really effected by a type and a power of beam girder. Interchange bridge with a iron girder which spread over a brackish water is very susceptible to corrosion where it can decrease the strength and resilience of the bridge.By doing an alternative study for planning back the structure of a bridge, especially for a main girder by using Prestress Concreteâ€™s profile and got the best bridge design structure, so hopefully it can solved that problem.Â This alternative study is using a reference standard of American Association of State Highway and Transportation Officials (AASTHO) for deciding dimension and the number of tendon, layout of placement cables and calculation of loss of voltage which are based on the book TY.LinThe result of calculation and discussion we got tendon dimension type ES-46 using a single tendon uncoated 7 wire super stands ASTMA-416 grade type with LOP about 17,75& and first prestress style 572747,548 Kg has loss prestress by 20% so that there is 470 tons of effective stress left with a last stress produced is aboutÂ - 165,670 to press and 16,133 to pull